Detecting Financial Misreporting with Real Production Activity: Evidence from an Electricity Consumption Analysis* - Allee, Kristian D.; Baik, Bok; Roh, Yongoh (Contemporary Accounting Research, 2021)
ABSTRACT This study examines whether a real production activity measure, firm‐level electricity consumption growth, is useful in detecting firm financial misreporting. Identifying proxies for a firm's underlying financial performance that are not a function of the firm's accounting system is essential for detection of misreporting. We propose that the difference between revenue growth and electricity consumption growth (i.e., growth wedge (GW)) is a useful signal of financial misreporting. Using electricity consumption data for Korean firms from 2006 to 2014, we find that the GW is positively associated with discretionary revenues and accruals and the likelihood of financial misreporting as proxied by accounting restatements, qualified audit opinions, and regulatory enforcement actions. The GW provides incremental information over firm characteristics and earnings management signals examined by prior research. Our findings are robust to a battery of additional tests, including within‐firm and industry comparisons that do not require access to cross‐sectional firm‐level electricity data. Overall, our study documents new evidence on the role of a real production activity measure from an independent reporting entity in detecting financial misreporting. Our evidence speaks to the potential usefulness of real activity metrics in forensic economics.